General Practitioners reduced benzodiazepine prescriptions in an intervention study: a multilevel application - Stewart, R; Niessen, W; Broer, J; Snijders, T; Haaijer-Ruskamp, F; Meyboom-De Jong, B (2007)
Objective: This study investigated the effects of general practitioner, patient, and prescription characteristics on the reduction of long-term benzodiazepine prescribing by sending a letter to chronic users. The data were analyzed with a method respecting the hierarchical data structure. Study Design and Setting: Data were obtained from 8,170 chronic users nested in 147 general practices. One thousand two hundred fifty-six chronic users in 19 general practices received a letter with the advice to reduce or stop the use of benzodiazepines after the general practitioners had attended a course on benzodiazepine use. In a three-level random intercept multilevel regression model, long-term prescribing of benzodiazepines was the dependent variable. Results: The reduction in benzodiazepine prescribing was significantly larger in the intervention than in the control group: 16% after 6 months and 14% after 12 months, respectively. The age of the patient, gender, and the interaction between age and gender were significant. The combination of the duration (long acting or short acting) with the type of benzodiazepine (anxiolytic or hypnotic) was an important pharmacological baseline covariate. Conclusions: The reduction of benzodiazepine prescribing was mainly explained by the letter intervention and individual patient characteristics. Multilevel analysis was a worthwhile method for application in this study with its unbalanced design. © 2007 Elsevier Inc. All rights reserved.